Production amalgamation's “Belaruskali” potash delivery system analysis from logistic positions - Kolos, Maxim (Transport, 2006)
Belarus is one of the largest manufacturers of potash fertilizers. Geographical remoteness from commodity markets and absence of its own exit to sea require transshipment of production in foreign seaports. In this article, the author is analyzing, deriving from logistic considerations, according to which principles of such delivery system should be designed, what can be the criterion of its efficiency, how volumes of cargo transported through various channels influence self‐organizing capacity of the system as a whole, and what is the synergetic effect on the logistic system. The questions of designing logistic systems considered in this article on the example of potash fertilizers are, in many respects, common to all Byelorussian exporters.First Published Online: 27 Oct 2010